A landscaping review of interventions to promote respectful maternal care in Africa: Opportunities to advance innovation and accountability. (December 2022) - Diamond-Smith, Nadia; Lin, Sunny; Peca, Emily; Walker, Dilys
Abstract: Objective: In the past decade, global recognition of the need to address disrespect and abuse (also described as mistreatment of women) and promote respectful maternal care in facility-based childbirth has increased. While many studies have documented gaps in respectful maternal care, little is known about the design and implementation of these interventions. Our aim was to summarize and describe respectful maternal care -promoting interventions during childbirth implemented in Africa. Design: We identified respectful maternal care -promoting interventions in Africa through a rapid scoping of peer-reviewed articles and gray literature, and a crowdsourcing survey distributed through stakeholder networks. Setting: Africa Participants: NA Measurements and findings: We identified 43 unique interventions implemented in 16 African countries, gathered from a crowdsourcing survey, gray and published literature between 2010 and 2020. Most interventions were implemented in East Africa ( N = 13). The interventions had various targets and were categorized into nine approaches, 60% of interventions focused on training providers about respectful maternal care and practice. About two thirds included multiple intervention approaches, and about two thirds addressed respectful maternal care beyond the period of childbirth. Few publications presented data on the effectiveness of the intervention, and those that did used a wide variety of indicators. Key conclusions and implications for practice: There is a reliance on provider training approaches to promote respectful maternal care and there are few examples of either engaging women in the community or adopting social accountability approaches. We encourage implementors to develop interventions targeting multiple approaches beyond provider training and consider delivery across pre-pregnancy, pregnancy, birth, and the postnatal periods. Finally, in order to effectively move from documenting respectful maternal care gaps to action and scale, we need global consensus on common indicators and measures of effectiveness for interventions promoting respectful care across the life course.